(untitled) (International journal of artificial intelligence, 2026)
Throughout human life, individuals experience various emotions such as joy, anger, fear, excitement, sadness, and others. These emotions not only reflect our internal experiences but also directly influence our decisions, behaviors, and relationships with others. Therefore, the issue of emotion regulation plays an important role in psychology and everyday life.